CRITICAL COMMUNICATIVE METHODOLOGY: TRANSFORMATIONS AND CHANGES IN THE S. XXI - Aitor Gómez González; Javier Díez-Palomar (Ediciones Universidad de Salamanca, 2009)
The educational and social analysis conducted on the current society increasingly discovers more dialogical values. To analyze this society a methodology that meets this increasingly complexity and dialogic character is needed. The critical communicative methodology responds to this new situation, helping to overcome educational and social inequalities and promoting social inclusion of groups who are in disadvantaged situations. In this article we present how through the critical communicative methodology we can carry out analysis of social and educational problems which can hardly be approached from more traditional methodologies. For this, we introduce briefly the main features of the society in which we find, the new challenges facing us and how the critical communicative methodology can help to overcome situations of social exclusion.